Barriers to initiating insulin therapy for patients with poorly controlled type 2 diabetes mellitus on maximum dose of oral agents in public sector primary health care centres in Cape Town, South Africa - Haque, Monirul (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.